Clinical and laboratory studies in four goats with leptospirosis out of a herd of goats - Dabak, M; Gül, Y; Kizil, Ö; Özdemir, V (Scientific Technical Research Council Turkey, 2001)
Four male goats aged 10-12 months showing clinical signs of leptospirosis out of a herd of 90 goats in the province of Elazig were used in this study. Having performed a systematic clinical examination of the sick animals, blood samples were taken from v. jugularis for heamatological (total leucocytes, erythrocytes, haemoglobin and PCV), biochemical (blood glucose, plasma proteins, albumin, globulin, total, direct and indirect bilirubin, aspartate amino transferase, urea and creatinin) and serological (microscopic agglutination test, MAT) analysis. Intramuscular penicillin+streptomycine, subcutaneous 40% urotropin solution and oral ammonioum chloride were administered daily. Two of the sick animals died while the other two recovered. Other animals showing no clear signs of the disease in the herd were vaccinated against the disease for prophylactic purposes. None of these animals developed the disease.
Leptospirozis Saptanan bir Keçi Sürüsünde Klinik ve Laboratuvar Çalisçmalar
Keywords: leptospirosis; goat; treatment; prophylaxis